2014
DOI: 10.1080/14681994.2014.976997
|View full text |Cite
|
Sign up to set email alerts
|

The association of an open relationship orientation with health and happiness in a sample of older US adults

Abstract: Sexual activity over the life course is strongly associated with better health and greater personal happiness, yet the sexuality of aging adults has been a neglected topic. There is a lack of research on those with a consensually non-exclusive sexual relationship style regardless of age. This research examines whether such an orientation has positive effects on sexual frequency, health and personal happiness, and how this might inform counselors and therapists providing services to older adults. The authors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 47 publications
1
18
0
1
Order By: Relevance
“…The finding that such negative association emerged only for these individuals may indicate that unrestricted sociosexuality appears to be more problematic for CM relationships, possibly because it is associated with a greater likelihood of EDS. For those in a CNM relationship, although this association was non-significant, it actually reversed to a positive association (for a significant positive association between sociosexuality and relationship quality with an older sample of participants, see Fleckenstein & Cox, 2015;Rodrigues, Lopes, & Pereira, 2016b). Because past research has shown that individuals in CNM relationship do not perceive EDS as indicative of infidelity (Cohen, 2015), and because our findings suggest that EDS does not impair relationship quality among these individuals, it is possible that EDS is not a violation of trust, honesty and openness that characterizes CNM relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that such negative association emerged only for these individuals may indicate that unrestricted sociosexuality appears to be more problematic for CM relationships, possibly because it is associated with a greater likelihood of EDS. For those in a CNM relationship, although this association was non-significant, it actually reversed to a positive association (for a significant positive association between sociosexuality and relationship quality with an older sample of participants, see Fleckenstein & Cox, 2015;Rodrigues, Lopes, & Pereira, 2016b). Because past research has shown that individuals in CNM relationship do not perceive EDS as indicative of infidelity (Cohen, 2015), and because our findings suggest that EDS does not impair relationship quality among these individuals, it is possible that EDS is not a violation of trust, honesty and openness that characterizes CNM relationships.…”
Section: Discussionmentioning
confidence: 99%
“…49 Therefore, being registered on Second Love and engaging in extradyadic sex is not perceived as a sign of relationship problems, or as a need for intimacy that is not being met within the primary relationship. Having such agreement with the partner, extradyadic sex can increase personal well-being and happiness 21 and increase relationship satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has also shown that individuals in SNMR do not perceive extradyadic sex within mutually consented boundaries as infidelity, 18 and that engaging in such behaviors can improve personal happiness. 21 As happiness is associated with relationship quality, 44 we expected a positive association between sociosexuality and relationship satisfaction for these individuals. Based on recent findings on infidelity, we predicted no gender differences in these associations.…”
Section: Current Study and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…More strongly, empirical research suggests that polyamorous relationships are better than monogamous ones in several respects. For example, Fleckenstein and Cox (), in their study of older people in non‐exclusive sexual relationships, found that irrespective of age or relationship type “the non‐exclusive sample generally outscored the relevant comparison group of the general population on sexual frequency, number of sexual partners, and self‐reported health and personal happiness” (p. 112). There was no evidence to suggest exclusive marriage supported these factors, even in later life when romantic profundity is most expected as a function of experience, proximity, and time spent together.…”
Section: Polyamorous Profunditymentioning
confidence: 99%